A Descriptive Study On Vocabulary Teaching-Learning Process At The Fourth Year Of SD N 1 Gedongan, Karanganyar In 2011/2012 Academic Year - Sundari, Rizki Dyah, Drs. Djoko Srijono, M. Hum, Dr. Anam Sutopo, M. Hum (2013)
The research aims at describing the process of teaching-learning vocabulary at the fourth year of SD N 1 Gedongan, Karanganyar. The research conducted to describe the process of teaching-learning vocabulary, the difficulties faced, and the problem solving applied by the teacher at the fourth year of SD N 1 Gedongan , Karanganyar. In this research, the data are derived from event, informant, and document. There are three kinds of methods in collecting the data, namely conducting observation, interviewing, and analyzing documents. The data are information related to the process of teaching learning vocabulary, the difficulties and the problem solving applied by the teacher at the fourth year of SD N 1 Gedongan, Karanganyar. The result of the analysis shows that the process of teaching-learning vocabulary in SD N 1 Gedongan, Karanganyar has seven steps in every process. The teacher applied Grammar Translation Method and Direct Method to teach. The difficulties faced by the teacher are the students less discipline to learn English, the students have no motivation to learn English, there is no media available to convoy the material in school, and vocabulary acquirement difficulties. The strategies implemented by teacher in solving the difficulties are motivating the students if learning English is important, optimal the media in round the school to convoy the material in order to make the students interest in English and the teacher asked the student to memorize the words in the target language.